The Bioclimatic Chart Informed Urban Design for Debre Berhan Town - Metaferia, Kifle Tadesse (Journal of Urban Development Studies, 2022)
Discomfort occurs when the surrounding average temperature is below 20oC and above 27oC while surround relative humidity is under 20% and above 80% which is Thermal Comfort principles. Due to this, in the case of Debre Berhan, most of the time discomfort was occurred in different seasons and bioclimatic chart of the towns hadn’t been developed to get it the cooling demand to employ appropriate strategies that are shown by the bioclimatic chart. Thus, the purpose of this study was to inform Bioclimatic chart of Debre Berhan Town by focusing on developing neutral temperature and measure the thermal sensation of the resident’s perception by sematic scale. Both primary and secondary data was analyzed by qualitative and quantitative research approach. Temperature, humidity and air speed were the major types of microclimate data to analyze in TMY (Typical Metrological Year) and perception of the residents by sematic scale. Based on this, the findings of the study indicated that for Debre Berhan town, the neutral temperature of Debre Berhan was 27.17oC which exceeded by 1.16oC from the standard. The sematic scale highlighted that the temperature perception of the residents was slightly cool, with slightly dry humidity and very low wind speed. Finally, the comfort zone is between 11.68oC to 29.24oC. Hence, Debre Berhan town needs cooling strategies especially from June end to January of the year.